Social network influences on new mothers' infant sleep adjustments. (January 2021) - Cornwell, Benjamin; Yan, Xuewen; Carlin, Rebecca F.; Fu, Linda; Wang, Jichuan; Moon, Rachel Y.
Abstract: Despite public awareness campaigns, some parents continue to engage in infant sleep practices that are considered risky by health experts, such as bedsharing or placing their infants on their stomachs. This study examines the role their social networks play in shaping parents' responsiveness to new information and/or suggestions about how they should place their infants for sleep, paying attention to the respective effects of health professionals and their close interpersonal ties. We collected data from a sample of 323 new mothers in Washington, D.C., who described their infant sleep practices and perceived personal social networks. We find evidence that mothers' social networks play a significant role in the likelihood that they adjust their infant sleep practices within the first few months of their infants' lives. Mothers are more likely to change sleep practices when health professionals and/or (lay) family members advise them to do so. The influence of network members is not always positive. For mothers who initially follow safe practices, their probability of change increases if their network members substantially espouse unsafe practices. Among mothers with initially unsafe practices, network members' level of support for safe sleep practices is not predictive of the likelihood of sleep practice change. Implications for potential interventions are discussed. Highlights: Social networks affect mothers' propensity to adjust infant sleep practices. Mothers tend to adjust their practices when health providers advise them to do so. Mothers also tend to adjust their practices in response to family members' advice. The influence of personal network members may be negative for infants' sleep safety.